Impact of Surface Properties of Core Material on the Stability of Hot Melt-Coated Multiparticulate Systems - Sonja Schertel; Sharareh Salar-Behzadi; Andreas Zimmer (MDPI AG, 2021)
Hot melt coating (HMC) of an active pharmaceutical ingredient (API) powder with lipid-based excipients is an innovative method for manufacturing patient-convenient dosage forms. However, drug release instability is still its main industrial challenge. The correlation between the unstable pharmaceutical product performance with the solid-state alteration of lipids is currently well-investigated. The remaining problem is the inconsistent release alteration of different APIs coated with the same lipid after storage, such as faster release in some cases and slower release in others. The interaction between API surface and lipid-based coating and its alteration during storage were investigated in this work. The surface properties of five different APIs and the coating composition of tripalmitin and polysorbate 65 were screened via Washburn and pendant drop methods, respectively. Metformin hydrochloride and hydrochlorothiazide particles were each coated with the coating composition. The water sorption alteration of coated particles and the crystal growth of tripalmitin in the coating after storage were measured via tensiometry and X-ray diffraction. The cleavage work necessary to overcome the adhesion of coating composition on the core surface was calculated for each API. The accelerated release of the polar core (metformin) after storage was correlated with a low cleavage work and a distinctive phase separation. In contrast, a decelerated release of the hydrophobic core (hydrochlorothiazide) was favored by the crystal growth of the lipid-based coating. The gained knowledge can be used to design the product stability during the formulation development.